Bio-inspired assembling/mineralization process as a flexible approach to develop new smart scaffolds for the regeneration of complex anatomical regions. Issue 12 (September 2016) - Sprio, Simone; Sandri, Monica; Iafisco, Michele; Panseri, Silvia; Adamiano, Alessio; Montesi, Monica; Campodoni, Elisabetta; Tampieri, Anna
Abstract: Bio-inspired synthesis of smart biomaterials is an emerging nano-technological approach to develop new solutions for an ever-raising number of patients affected by degenerative and disabling pathologies. Particularly for purpose of tissue regeneration, the new materials should function as scaffolds with high mimicry of host tissues, in order to instruct cells to perform their task. Due to the complexity of living tissues and limitations of the current fabrication methods, synthesis methods reproducing the biologic processes may exploit the huge information inherent in macromolecular matrices, to build complex nano-composites with regenerative ability. As an example the assembling/mineralization phenomena involved in hard tissues can be mimicked to achieve smart devices able to regenerate different tissues such as joints and periodontium. Besides, the implementation of this approach with remote activation by low magnetic fields of bio-resorbable superparamagnetic apatite nano-phases, may provide new devices enabling activation on demand suitable for non-invasive and more effective therapies.